Association Between Personal Hygiene, Clean and Healthy Living Behavior (PHBS), and Scabies Incidence Among Students of Pondok Pesantren Darussalamah - Setiajaya, Arif; Zulaicha, Annisaa Siti; N, Natalina; Ardiani, Nurika Septa; Prasetio, Bambang (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
Scabies, caused by the mite Sarcoptes scabiei var. hominis, is a contagious skin disease often found in densely populated environments like dormitories, prisons, and Islamic boarding schools. This study investigates the relationship between personal hygiene, Clean and Healthy Living Behavior (PHBS), and the incidence of scabies among students at Darussalamah Islamic Boarding School. The examined variables include skin cleanliness, hand and nail hygiene, towel hygiene, genital hygiene, clothing cleanliness, and bed and linen hygiene. Using total sampling, all students participated, with data collected through observation, interviews, and questionnaires, analyzed via the chi-square test. Results showed 82.6% of students experienced scabies, with significant associations found between personal hygiene variables and scabies incidence, except for environmental cleanliness (p-value = 0.069). The study provides two primary and two alternative strategies to prevent scabies outbreaks, emphasizing the importance of improving hygiene practices to reduce the disease's prevalence in such settings.